Community-based Photogrammetric Assessment of Nasal Angles among Adults in the Garhwal Himalayas, Uttarakhand, India - Niyati Airan; Anil Kumar Dwivedi; Ananya Sharma; Viyom Agarwal (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: The nose has long been known to hold an important place in the medical sphere, owing to its important functions in olfaction and respiration. Its normal morphology and morphometry are also crucial for determining facial aesthetics. Different types of nasal deformities are also seen to be associated with various congenital anomalies. Anthropometry of the nose varies with age, gender and ethnicity. Aim: To explore region-, ethnic-, and gender-specific nasal angulations of the adult population of Garhwal, Himalayas, Uttarakhand, India. Materials and Methods: This community-based crosssectional observational study was conducted at the Department of Anatomy, Veer Chandra Singh Garhwali Government Institute of Medical Science and Research, Srinagar Garhwal, Uttarakhand, India, from July 2024 to June 2025. Multistage sampling was applied to measure 141 males and 105 females residing in the Garhwal Himalayas, using the photogrammetric method. Nasofrontal, nasofacial, nasolabial, nasal-tip and interalar angles were measured employing the Magnus Analytics MagVision application. Descriptive (Mean and Standard deviation) and inferential (Independent t-test and Welch’s t-test) statistics were done by Statistical Package for Social Sciences (SPSS) software, with p